Necessity of Kids wear Safety Regulations for India: Viewpoint of Retailers - Kothari, Vasant; Mathews, Soney (2016)
Product safety refers to the production, distribution, and sale of products that from various perspectives are either potentially unsafe or inherently unsafe to consumer use. In order to make sure that the product which consumer is buying is safe, there should be some safety standards. These standards are normally designed to ensure the safety of products, activities or processes etc. The Indian kidswear market is going to see the tremendous growth. It is important to note that no regulations for kidswear safety are in place in India whereas in developed nation there is legislative control on Kidswear merchandise. The main aim of this study is to find out the necessity of safety regulations for Indian market from the retailers’ point of view. For the study, 110 retailers were selected through stratified random sampling from Bengaluru, India and information was collected with the help of structured and well-designed questionnaire. The study concludes that, as per Indian retailers all the kidswear in India are not and therefore parents are vigilant while purchasing the same. Most of the retailers also agree that parents do discuss about the safety-related issue with them. Indian retailers are in favor of having standard regulations for the kidswear for Indian market.